Two-year retrospective analysis of repeated emergency service admissions in a secondary stage hospital: Diagnosis-based evaluation - Eriten, Semih (The European Research Journal, 2025)
Objective: This study aims to evaluate the characteristics of repeated emergency department (ED) visits in a secondary care hospital over a two-year period and analyze trends across different diagnostic categories. Methods: A retrospective analysis was conducted on ED visit data from January 2023 to September 2024. Patient demographics, primary diagnoses, and visit frequencies were examined. Statistical analyses were performed to compare trends between 2023 and 2024, with subgroup analyses based on age and gender. Results: The repeated visit rate was found to be 25.8% in 2023 and 26.0% in 2024, consistent with existing literature. The most common diagnosis was upper respiratory tract infections (URTI), accounting for 109,067 visits in 2023 and 83,655 visits in 2024, showing a significant decline. In contrast, general medical examinations and gastroenteritis cases increased in 2024 compared to 2023, indicating a potential shift in healthcare-seeking behavior. Myalgia ranked second, with 26,727 cases in 2023 and 21,225 in 2024, predominantly affecting middle-aged women. Falls and soft tissue disorders, ranked third, were more prevalent in male patients, with 24,351 cases in 2023 and 19,616 in 2024. Age-specific trends showed that trauma-related conditions were most common in children (0-10 years), while musculoskeletal and cardiovascular disorders increased with age. Gender distribution analysis indicated that headache and acute cystitis were more frequent in women, whereas falls and cardiovascular diseases were more common in men. Conclusions: The findings highlight the need for better coordination between emergency and primary healthcare services to reduce unnecessary repeat visits. The shift in diagnostic trends suggests that regional healthcare planning should adapt to evolving patient needs. Future research should explore psychosocial factors contributing to repeat visits and assess the economic burden of ED overutilization.